A new equine peripheral caries grading system: Are the caries likely active or inactive?. (29th October 2020) - Jackson, Kirsten; Kelty, Erin; Tennant, Marc
Abstract: Background: Equine peripheral caries can be a significant welfare issue in affected horses. Recent work has shown that complete reversal of the condition may be possible if the primary risk factor can be identified and corrected. Determining whether caries are active (deteriorating) or inactive (improving) is of vital importance when formulating a management and treatment plan. A new grading system is proposed that looks at whether caries are likely active or inactive to assist clinicians deciding whether intervention is required. Objectives: To examine the reliability of an alternative grading method for equine peripheral caries. Study design: Online survey of veterinary surgeons. Methods: Reviewers (n = 22) graded images of peripheral caries using three methods: the traditional grading system, a new research grading system and a new clinical grading system. Percentage agreement and Fleiss' kappa were used to examine the participant's agreement of the severity of caries. Results: All percentage agreements and Fleiss' kappa values were significantly greater than zero ( P < .001). The Fleiss' kappa for the new methods were higher (ranging from 0.48 to 0.58), but not significantly different from the traditional method (0.40). There was a high level of consistency in the assessment of caries as either active or inactive with both grading systems reporting over 80% agreement. Feedback on the grading systems was positive with over 90% of reviewers saying they were likely to use the system. Main limitations: The use of photographs provided some difficulties with image quality and judging whether the dentin was affected without an occlusal image. Conclusions: The new grading system produced a consistent estimate of caries severity and provided high levels of agreement on whether the caries were likely 'active' or 'inactive'. This is likely to be very useful clinically to assist practitioners to determine whether intervention is required.